2018
DOI: 10.1007/s10735-018-9758-3
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of secreted frizzled-related protein 1 (SFRP1) promoter downregulates Wnt/β-catenin activity in keloids

Abstract: Keloid, a benign skin disorder, forms during wound healing in genetically susceptible individuals. To better control keloid and understand the molecular mechanisms, this study screened gene hypermethylations of GEO database microarray data on keloids and identified the hypermethylation of the secreted frizzled related protein-1 (SFRP1) promoter. Subsequently, hypermethylation and mRNA and protein levels were assessed in 57 cases of keloid vs. normal skin tissues. Fibroblasts from tissues were isolated for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The treatment of 5-Aza-dc, as an inhibitor of DNA methyltransferase, appeared to conspicuously escalated SFRP1 level and coordinated Wnt/β-catenin activity in KFs. Furthermore, a functional verification experiment ulteriorly authenticated that downgrade DNMT1 instead of DNMT3a or DMNT3b was responsible for the hypermethylation of the SFRP1 promoter and upregulation of SFRP1 expression in KFs [52]. These two findings indicated that DNA methylation and histone acetylation might cooperatively participate in regulating SFRP1 expression, and the mutual relationship seems to be bidirectional with each able to affect the other.…”
Section: Mechanisms Of Dna Methylation In Keloidmentioning
confidence: 91%
See 1 more Smart Citation
“…The treatment of 5-Aza-dc, as an inhibitor of DNA methyltransferase, appeared to conspicuously escalated SFRP1 level and coordinated Wnt/β-catenin activity in KFs. Furthermore, a functional verification experiment ulteriorly authenticated that downgrade DNMT1 instead of DNMT3a or DMNT3b was responsible for the hypermethylation of the SFRP1 promoter and upregulation of SFRP1 expression in KFs [52]. These two findings indicated that DNA methylation and histone acetylation might cooperatively participate in regulating SFRP1 expression, and the mutual relationship seems to be bidirectional with each able to affect the other.…”
Section: Mechanisms Of Dna Methylation In Keloidmentioning
confidence: 91%
“…Subsequently, the appliance of Trichostatin A (TSA) and 5-Aza-2′-deoxycytidine (5-aza-dc) determined that SFRP1 expression in KFs was increased almost 15-fold by TSA but not by 5-aza-dc, speculating that silencing of SFRP1 was not due to hypermethylation but histone modification. However, recent studies by Liu et al presented that the lost SFRP1 expression due to the hypermethylation of the SFRP1 promoter likewise might play a vital role in the pathological progress of keloid [52]. The treatment of 5-Aza-dc, as an inhibitor of DNA methyltransferase, appeared to conspicuously escalated SFRP1 level and coordinated Wnt/β-catenin activity in KFs.…”
Section: Mechanisms Of Dna Methylation In Keloidmentioning
confidence: 98%
“…Zhang found the genes related to the pathogenesis of oralsquarous cell carcinoma (OSCC) utilizing bioinformatics analysis, and further verified these molecules might lead to OSCC through the PI3K‐AKT pathway, suggesting the relevant molecules may be a molecular target for specific diagnosis and therapy (Zhang, Feng, et al, 2018; Zhang, Zhang, et al, 2018). In addition, Liu found abnormally expressed molecules in multiple scar tissues by bioinformatics analysis and further verified that SFRP1(OMIM:604156) might take part in the occurrence of scar by regulating Wnt/β‐catenin (Liu et al, 2018). However, there are few reports on the use of bioinformatics analysis to explore the mechanisms of acute tracheal injury and TS.…”
Section: Introductionmentioning
confidence: 85%
“…Fibroblasts were grown to 95%-100% confluency and then scratched in each well using a sterile 200 mL tip. 18 Without ESI-09 application, fibroblasts migrated from the edge of the scratch and completely covered the area cleared by the scratch 24 h after wounding. ESI-09 application increased the amount of time required for HKFs and HDFs to cover the same blank area, thus cell migration was significantly decreased by ESI-09 in a dose-dependent manner (Fig.…”
Section: Treatment With Esi-09 Reduces Proliferation and Migration Ofmentioning
confidence: 99%